2019
DOI: 10.1039/c8tc05357j
|View full text |Cite
|
Sign up to set email alerts
|

1,2-Diarylbenzene as fast T-type photochromic switch

Abstract: A novel fast T-type photochromic molecular system, 1,2-diarylbenzene, was successfully developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 36 publications
2
65
0
Order By: Relevance
“…This may indicate that the ring-closed species, being relatively insusceptible to oxidation by the presence of the C11 and C13 methyl groups, undergoes a fast thermal cycloreversion that precludes its spectroscopic detection. 53 We will return to this issue in section 2.2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may indicate that the ring-closed species, being relatively insusceptible to oxidation by the presence of the C11 and C13 methyl groups, undergoes a fast thermal cycloreversion that precludes its spectroscopic detection. 53 We will return to this issue in section 2.2 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, this indicates that the absence noted in section 2.1 of a change in the experimental absorption spectrum of Me 4 -1a upon irradiation with UV-light, is not related to the influence of the C11 and C13 methyls on the cycloreversion, but rather to their ability to prevent oxidation of the ring-closed species. 53 …”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27] Very recently, we have succeeded in developing a T-type photochromic compound, 1,2diarylbenzene (DAB) by only introducing a tetrafluorobenzene ring to the ethene bridge of a representative DAE, 1,2-bis(2-methyl-5-phenyl-3-thienyl)perfluorocyclopentene (Scheme 1). 28 DAB (1a) undergoes photocyclization upon irradiation with ultraviolet (UV) light and fast thermal cycloreversion with a t1/2 of 130 ms at 298 K. However, 1a has several limitations in practical applications such as photochromic ophthalmic lenses. Specifically, 1a has almost no absorption in the UV-A region (315-400 nm), and the absorbance at visible region of the closed-ring isomer 1b upon irradiation with UV (313 nm) light is very small because of the extremely rapid thermal cycloreversion.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained activation energies (74 kJ.mol -1 for BTP1 c and 67 kJ.mol -1 for 1Y c ) are clearly lower than those observed for P-type classical DTEs (based on the perfluorocyclopentene core) that show typical values as large as 140 kJ.mol -1 [2,26,43]. They are nevertheless comparable to other fast bleaching systems like dithienyl thiazole derivatives [44] (80 to 90 kJ.mol -1 ), phenanthrene-based compounds [45] (50-60 kJ.mol -1 ) as well as perfluorobenzene-based compounds [29] (66 kJ.mol -1 ) and clearly reveal that the origin of this fast bleaching is the low stability of the closed form that correlates with low activation energies for the cycloreversion reaction. This is further confirmed by theoretical investigations (see below).…”
Section: Study Of Photochromism By 1 H Nmr Spectroscopy At Variable Tmentioning
confidence: 70%
“…Typically, DAE with phenanthrene bridges [27][28] show low photoconversions and fast thermal bleaching of their closed isomer due to the loss of aromaticity upon photocyclisation. For example, a central fluorinated benzene ring can provide fast T-type photochromic DAE with a half-life of 130 ms at room temperature [29]. Recently, Diederich et al demonstrated that DAE with a central pyrazine bridge like 2,3-bis(2,5-dimethylthiophen-3-yl)pyrazine are also T-photochromes with a thermal half-life of ca.…”
Section: Introductionmentioning
confidence: 99%